Introduction to the Review Symposium - Decolonizations: Cleaving Gestures that Refuse the Alien Call for Identity Politics - Bhogal, Balbinder (Religions of South Asia, 2012)
Here follows a general introduction to this special issue of RoSA, which takes the form of a Review Forum discussing Arvind-Pal S. Mandair’s Religion and the Specter of the West: Sikhism, India, Postcoloniality, and the Politics of Translation (hereafter RSW), published in 2009 by Columbia University Press.